Exploring Trust and Engagement: A Qualitative Evaluation of the Relationship Between Clinicians and Healthcare Leaders at Academic Medical Centers - Keller EJ; Sehgal N; Ryu RK; Chrisman H; Vogelzang RK; Shanafelt TD (Journal of Healthcare Leadership)
Eric J Keller,1 Niraj Sehgal,2 Robert K Ryu,3 Howard Chrisman,4 Robert K Vogelzang,4 Tait D Shanafelt2 1Department of Radiology, Stanford Health Care, Stanford, CA, USA; 2Department of Medicine, Stanford Health Care, Stanford, CA, USA; 3Department of Radiology, University of Colorado, Aurora, CO, USA; 4Department of Radiology, Northwestern Medicine, Chicago, IL, USACorrespondence: Eric J Keller, Email ejkeller607@gmail.comBackground: Dynamics between clinicians and healthcare leaders are critical in determining the culture and success of Academic Medical Centers (AMCs). These dynamics are complex, making it challenging to develop effective means of improving these relationships. This study sought to characterize and compare relationships between clinicians and healthcare leaders at three AMCs to develop more effective means of improving healthcare organization cultures.Materials and Methods: The authors interviewed clinicians, clinician leaders, and operational leaders at three AMCs about their role, perceived dynamics between clinicians and healthcare leaders, and ideal leadership. Interviews continued until additional interviews stopped revealing new information at each organization, requiring a total of 92 participants (49% male, 54% clinicians, 22% clinician-leaders, 24% operational leaders). Interview transcripts were systematically analyzed based on constructivist grounded theory and content analysis for key themes.Results and discussion: The perceived most pressing issues at each AMC varied across three key cultural levels: organization, department, and practice. When interventions targeted levels distinct from the level perceived most pressing, they tended to exacerbate existing issues and further undermine trust and engagement between clinicians and healthcare leaders. Clinicians and healthcare leaders across AMCs described similar traits of ideal leadership but exhibited different understandings of what those traits meant in application. Cultural dynamics were also challenged by professional cultural differences between the three groups and barriers such as differences in status, location, and background. Limitations of this study included its cross-sectional nature and potential sampling bias.Conclusion: The level of organizational culture where the greatest tension exists between clinicians and healthcare leaders varies by three key levels. Discerning which level of organizational culture represents the greatest local opportunity can inform the design of more targeted interventions to improve dynamics between clinicians and healthcare leaders seeking to foster more constructive partnerships.Keywords: organizational culture, academic medical center, cultural dynamics, cultural levels